Computational Thinking Guiding Change in Online Education - Quinn, Brigette J. (Journal of Medical Biomedical and Applied Sciences, 2016)
As a result of instant access to data, information and knowledge anywhere, anytime, todayâs students have rapidly acquired educational opportunities. Online education continues to grow at a pace much faster than face to face enrollments. There is a need for faculty development and training who can teach with technology, design and develop online courses in order to meet the increasing student demand. Faculty barriers to online education include loss of interpersonal student relationships, technology challenges, pedagogical concerns, institutional policy problems and unidentified support or compensation for all associated processes. At the crossroads of problem identification, strategy, and adoption of innovation, Computation Thinking (CT) offers a logical, exploratory, expandable and collaborative way of solving a complex problem in a state of change. This paper aims to summarize and synthesize the literature on both CT and faculty barriers to adoption of online education. A further aim is to offer suggestions for collaborative faculty design and development opportunities in exploring their own experience with online education using CT as a framework for problem-solving.